Physicochemical and organoleptic characteristics of instant rice with the addition of moringa leaf (Moringa Oleifera l) and butterfly pea (Clitoria Ternatea) extract produce of cabinet dryer - Hariadi, Hari; Elizabeth, Roosganda; Nurmalinda, Nurmalinda; Soetiarso, Thomas Agoes; Nurmaulidia, Aulia (International Journal of Innovative Research and Scientific Studies, 2025)
Instant rice is a processed rice product that has been cooked and then dried so that the product can be stored for a long period of time, but can be served in a shorter period of time. This research was conducted to determine the difference between instant rice with moringa extract and instant rice with butterfly pea flower extract. The tests carried out in this research were physicochemical characteristics and organoleptic tests. The highest treatment for instant rice with the addition of Moringa extract yield analysis was obtained in the A3B3 treatment 78.88 ± 4.07b, the highest rehydration time was obtained in the A3B1 treatment 5.74 ± 0.47c, the highest kamba density was obtained in the A2B1 treatment 0.65 ± 0, 06c, the highest water content was obtained by the A1B1 treatment 8.03 ± 1.16d, the highest ash content was obtained by the A1B3 treatment 0.98 ± 0.01a, the highest antioxidant content was obtained by the A1B1 treatment 111.42 ± 0.87a, the highest protein content was obtained by the A3B1 treatment 9.40±0.24c. The results of the organoleptic test that are widely preferred are the A1B1 treatment (10% Moringa extract; 50ºC drying temperature). Then, the research results for instant rice using butterfly pea flower extract were obtained, namely the highest kamba density was obtained in the P1W1 treatment (0.66 ± 0.01d), the highest yield was obtained in the P3W2 treatment (81.00 ± 2.12e), the fastest rehydration time was obtained in the P3W3 treatment (4.35 ± 1.08a), then the results of the chemical analysis of the highest water content were obtained in the P2W1 treatment (7.02 ± 0.04g), the highest ash content was obtained in the P3W1 treatment (1.10 ± 0, 07ab), the highest antioxidant levels were obtained in the P1W1 treatment (319.58 ± 0.64g). The results of the organoleptic test for the most preferred formulation are the P2W2 treatment (20% butterfly pea flower extract and 60ºC drying temperature).